Bayuda and its neighbours - Obłuski, Artur,; Paner, Henryk,; Masojć, Mirosław, (Nubia : studies in the archaeology and history of northeast Africa ;, 2021)
The Bayuda, although an arid desert located in modern-day Sudan, has nonetheless been inhabited, farmed, worshipped in, and fought over by humans from the Palaeolithic onwards. Yet despite the longevity of its human occupation, the region has only in recent years become the focus of more intensive scholarly research. This volume, the first in a series dedicated to exploring the archaeology and history of Northeast Africa, aims to build on this trend by drawing together the very latest archaeological research and data and shedding light on how the Bayuda Desert and its environs were transformed into a cultural landscape. The contributions gathered here introduce, examine, and (re)assess a number of important issues, many of which are new in the archaeology of Nubia, as well as considering them against a broader comparative background. From climate change over the past millennia - and its far-reaching consequences in the present - through to an examination of the cultural influences of the Kingdom of Kerma, and from analysis of funeral rites through to interpretations of rock art, forgotten trade routes, and the commerce in cattle and slaves, this insightful volume offers a wealth of new information into the history of ancient Nubia.